Analysis of The Weakness Factors of Baitul Maal Hidayatullah (BMH) Yogyakarta in Raising Islamic Philanthropy Funds - Edi Santosa; Kamsi Kamsi; Sunaryati Sunaryati (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2022)
LAZNAS Baitul Maal Hidayatullah (BMH), which has been initially considered successful, in reality, shows a failure in terms of collecting zakat funds. BMH has received various awards from the Marketing Award, BAZNAS Award, and Anugerah Syariah Republika. However, the collection of zakat funds and the number of muzakki are very low and tend to decrease from year to year. In 2019, the number of muzakki was only 14.38%, and the zakat funds collected were only 11.7% of the total funds. This research aims to investigate what internal and external factors caused this decreasing trend. Employing interviews with the BMH leaders and employees, this study found that the internal factors of the low collection of zakat funds were: 1) The funds targeted by BMH from zakat were much lower than the other sources, only 32.66%; 2) BMH only followed the will of the donors; 3) BMH did not ask the donors whether they had paid zakat; 4) BMH felt uncomfortable to ask the donors whether they had paid zakat. Meanwhile, the external cause was that the donors tended to be more interested in choosing the programs offered by BMH rather than paying zakat.